KONTRIBUSI PENGGUNAAN SOFTWARE MACROMEDIA FLASH VERSI 8.0 TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA SMA - Rifqi Hidayat; Desy Lusiyana; Rinaldi Hariang Kara Zhan (Integral : Pendidikan Matematika, 2017)
This study examines the relationship between Macromedia Flash Software version 8.0 the ability of understanding mathematical concepts. This study is based on the performance of most of the students of SMAN 1 Pasawahan still lack understanding a concept when dealing with mathematical problems in learning in class. So when learning takes place and when faced with the issue of disadvantaged students to understand the concept and unable to resolve a given problem. The method used in this study is a quasi-experimental method. The study design used NonequivalentControl Group Design with correlation techniques. This method is used to see how strong and how much influence the Macromedia Flash software version 8.0 the ability of understanding of the concept. The population in this study were all students of SMAN 1 Pasawahan the academic year 2017/2018, the study sample was taken bysampling purposive of 56 students. The instrument used in this study is in the form of test descriptions understanding of the concept and scale of Macromedia Flashsoftware version 8.0. The results showed that there is a positive and significant relationship between Macromedia Flash software version 8.0 with the capability of understanding the concept. That is, the Macromedia Flash software 8.0 version ofcan be used to improve understanding of the concept. As well as Macromedia Flashsoftware version 8.0 has contributed 23.5% to the ability of understanding the concept, the rest of 76.5% is influenced by other variables not examined in this study.Keywords: Contributions, Macromedia Flash Version 8.0 and Capabilities ConceptTraining